Exploring the Application of Focusky-Based Presentation Media on Students’ Creative Writing in Indonesian University Context - Sitti Rahmawati; Muliadi Muliadi (ELT Worldwide: Journal of English Language Teaching, 2020)
Globally, students have long familiarized with utilizng a presentation program from Microsoft named Powerpoint, this program is good just not enough to attract the attention of students’ creativity. It is necessary a program that can not only be used to display concepts but also be able to attract the attention of students while presenting. The program in question is Focusky, in addition to being easy to use the program is also able to display slides with zoom in-zoom out effect with friendly facilities and object effects galore making this program very suitable used by students in presenting their tasks in front of the class. This study employs a qualitative descriptive study by conducting data collection through books and other literature as the main object.  Descriptive analysis method provides a clear, objective, systematic, analytical and critical picture and description of the application of focusky presentation media to the creative writing of Unuiversity students. Students in general, for example in the Faculty of Literature UMI do not have the same information technology capabilities (evenly) where there are those capable while some who are less in designing presentations. Hence, utilizing focusky will help students who could make creative presentations media to the best of their abilites.  Focusky-based presentation acts as an alternative to support students creativity that is very appropriate to apply to creative writing ideas and motivate students during presentations in higher education setting.